A new inactivated Tritrichomonas foetus vaccine that improves genital clearance of the infection and calving intervals in cattle - Ortega-Mora, Luis Miguel; Sánchez-Sánchez, Roberto; Rojo-Montejo, Silvia; Román-Trufero, Alicia; Montenegro-Gregorio, Dolores; Puentes-Colorado, Eugenia; Parra-Romero, Alberto; Regidor-Cerrillo, Javier; Osoro, Koldo; Collantes-Fernández, Esther (Frontiers in Veterinary Science, 2022)
Bovine trichomonosis is a sexually transmitted disease that is a primary cause of early reproductive failure in cattle. The aim of the present study was to develop a vaccine formulation based on Tritrichomonas foetus trophozoites inactivated by lyophilization and Quil-A-adjuvanted. The safety, immunogenicity and efficacy of this new vaccine formulation (Trichobovis®) administered by two routes (subcutaneous: SC, and intravulvar: IVU) were compared with a commercial vaccine (TrichGuard®) in a well-established experimental bovine model of genital T. foetus infection. The new vaccine was considered safe in cattle because only mild local reactions were found in the vaccination area, which disappeared 3 weeks after administration. Cows immunized with Trichobovis cleared the infection faster than the non-immunized/challenged group (27–28 vs. 60 days; P < 0.05). Not significant differences were observed with the commercial vaccine respect to the positive control group, or between SC and IVU routes. The new vaccine stimulated high serum anti-T. foetus IgG and genital IgA levels and generated an IgG booster effect similar to TrichGuard. IgA levels were associated with significantly earlier genital clearance of T. foetus in cows immunized with Trichobovis by SC route (G1A) or TrichGuard (G2). The strongest association was found in the group G1A on day 14 post-infection (p.i.) (r = −0.74) and in G2 on day 35 p.i. (r = −0.71). The efficacy of vaccination using Trichobovis on the reproductive performance was also investigated under field conditions in a herd where T. foetus was present. The calving intervals were significantly reduced by 45.2 days (P < 0.05), calves were born 28 days earlier (P < 0.05) and an increase of 8.7% in the calving rate (P > 0.05) was observed in the vaccinated group. These results demonstrate that Trichobovis improved the reproductive performance under field conditions in herds where T. foetus infection is present.